Repositioning Pesantren Education as the Basis of Islamic Education in Indonesia - Mohammad Ahyan Yusuf Sya'bani (DIDAKTIKA, 2023)
Today's post-modern era increasingly shows how complex the problem of pesantren is. Even pesantren has long existed in the archipelago can represent authentic education and able to face the challenges of an era. In the aspect of kiai, santri, learning mechanisms, establishment and implementation, infrastructure facilities in both huts and places of worship, the surrounding community that serves as a party that contributes to the implementation of pesantren, and many others. All of this is drawn to the contextualization of the post-modern era and globalization, which will fundamentally change all aspects of education in the pesantren. Whatever the purpose of the research is knowing the conceptualization of Islamic boarding schools education as well as the repositioning of Islamic boarding schools, especially in the digital era, as an effort to strengthen the existence of Islamic boarding schools. The research method used is a qualitative research method by choosing the literature research. Literature research is useful in reviewing about repositioning pesantren education as the basis of Islamic education in Indonesia. Therefore, the results of this study show that the peculiarities of pesantren are the main point in a pesantren education that needs to be redefined in the post-modern era and the midst of globalization currents such as Islamic learning, kiai, systems, and learning strategies. These elements of education in the present have been able to exist and adapt to the contextualization of the times as a whole so that pesantren education can continue to survive and even develop and advance